PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING BERBANTUAN LIVEWORKSHEETS PADA MATERI KELILING BANGUN DATAR DI KELAS V SEKOLAH DASAR - Devitha Yelsa; Masniladevi; Yullys Helsa; Salmaini Safitri Syam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by passive students and a lack of variety in the presentation of material, which led to low motivation to learn and poor understanding of mathematical concepts, particularly the perimeter of flat shapes. This study aims to develop a valid and practical e-LKPD based on Problem Based Learning assisted by Liveworksheets. The type of research used is Research and Development (R&D). This research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The subjects of this study were fifth-grade students at SDN 03 Aur Tajungkang and SDN 10 Tanah Lapang. Data were collected through validation and practicality questionnaires and analyzed descriptively and quantitatively. The results of the study showed the validity of the results obtained was “Very Valid” with a percentage of 91% for subject matter experts, 93% for language experts, and 99% for media experts. The practicality results showed the category “Very Practical” with a percentage of 96% in the teacher practicality test and 96% in the student practicality test.